Prolongation of QT Interval in ECG: A Hidden Complication of Cirrhotic Liver Disease - Ajeet Kumar; Syeda Urooj Riaz; Rajesh; Syed Hussain Mehdi Kazmi; Rajesh Kumar; Muhammad Ishaq Ghauri (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2019)
Objective: To  determine frequency of QT interval prolongation in ECG of patients with decompensated  liver cirrhosis in a tertiary care hospital of Karachi, Pakistan.